Civic education, civil society, and political mistrust in a developing democracy : the case of the Dominican Republic - Finkel, Steve E. (2000)
Explores the effect of donor-supported civic education programs on levels of citizen trust in institutions in the Dominican Repblic. Demonstrates that civic education had a direct, negative effect on participants' levels of institutional trust, with the greatest negative effect on trust in governmental bodies such as the army and the judicial system. Argues that this stems from the type of groups that conduct civic education in democratizing countries, many of which are not politically or socially neutral. Concludes with a discussion of these findings for theories of democracy and civil society and for donor-supported civic education programs.